The Meaning of The Clause in The May 2019 Issue of Radar Banten Newspaper and Its Implication With The Indonesian Language Learning Materials In Junior High School - Soleh (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
The porpuse of this research is (1) to analyze the meaning of the core clause in the May 2019 issue of Radar Banten news text and (2) to understand the implications of the new text with the Indonesian language learning materials in Junior High School. The research is carried out by equivalent and agih methods. Object in this research is a core clause found in the May 2019 issue of Radar Banten newspaper article. This research data consists of quotations that contain the significance of a core clause. This research source is a core clause found in the May 2019 issue of Radar Banten newspaper article. The data-collection technique uses speech and record. As for the data-analysis techniques used are the methods of equivalent with advanced techniques of choice and agih methods using two advanced techniques for immediate elements. The conclusion of this research is, 1). The meaning of the core clause in the May 2019 issue of Radar Banten news. 2) the implication of the core clause in the May 2019 issue of Radar Banten news with the Indonesian Language learning materials in Junior High School